0855 Primary Sleep Disorders And The Combined Outcome Of Poor Sleep Quality With Objective Short Sleep Duration In Older Persons. (27th May 2020) - Miner, B; Vaz Fragoso, C A; Han, L; Stone, K L; Redeker, N S; Yaggi, H K
Abstract: Introduction: Poor sleep quality with short sleep duration (SSD) is a high-risk phenotype that is likely to be associated with primary sleep disorders (obstructive sleep apnea [OSA], periodic limb movements of sleep [PLMS], and restless legs syndrome [RLS]) in older persons. We evaluated the associations among primary sleep disorders and this high-risk phenotype in older persons. Methods: Using data on 3, 058 men from the Osteoporotic Fractures in Men Sleep Study and 3, 127 women from the Study of Osteoporotic Fractures, mean ages 76 and 84 years, respectively, we evaluated cross-sectional associations between primary sleep disorders and the combined outcome of poor sleep quality with actigraphic SSD. In women, OSA and RLS were evaluated by self-report. In men, OSA and PLMS were evaluated by polysomnography and RLS by self-report. Poor sleep quality was defined by Pittsburgh Sleep Quality Index score >5 and SSD by average total sleep time ≤6 hours from wrist actigraphy (averaged over ~5 days). Men and women were evaluated separately. Multivariate logistic regression models also included demographics, self-reported chronic conditions, anxiety, depression, and medication use. Results: Poor sleep quality with actigraphic SSD was more prevalent in men (475 [15.6%]) than women (400 [13.1%]). In unadjusted models in men, odds of poor sleep quality with actigraphic SSD were significantly higher with OSA, PLMS, and RLS (ORs [95% Cis] = 1.99 [1.57, 2.52], 2.11 [1.41, 3.18], and 5.58 [2.51, 12.43], respectively). In multivariable models in men, odds of poor sleep quality with actigraphic SSD were significantly higher with OSA (1.59 [1.18, 2.14]) but not with PLMS or RLS. In unadjusted models in women, odds of poor sleep quality with actigraphic SSD were significantly higher with OSA (3.57 [0.40, 31.88]) and RLS (5.60 [3.04, 10.32]), but results were not significant in multivariable models in women. Conclusion: Older persons with primary sleep disorders have higher odds of poor sleep quality with actigraphic SSD. However, the predominant mechanisms underlying this high-risk phenotype may be driven more by medical and psychiatric comorbidity than by primary sleep disorders. Support: The American Academy of Sleep Medicine Foundation and the Yale Claude D. Pepper Older Americans Independence Center